Analysis of dose–TSH response effect of levothyroxine soft-gel formulation - Trimboli, Pierpaolo; Piticchio, Tommaso; Dadda, Zeno; Stramazzo, Ilaria; Gamarra, Elena; Ruinelli, Lorenzo; Virili, Camilla (Frontiers in Endocrinology, 2024)
Hypothyroidism is treated by daily assumption of levothyroxine (LT4). During the last years, soft gel caps of LT4 (LT4-C) have been commercialized, and its performance was optimal. Since guidelines recommend to dose LT4 according to the tablet preparation efficacy, the present study was undertaken to achieve data about the daily requirement, normalized per body weight, of LT4-C.Patients on LT4-C after total thyroidectomy and radioiodine for differentiated thyroid carcinoma were selected. There was no specific indication to have suppressed TSH (i.e., <0.5 or <0.1 mIU/L). Patients should maintain stable LT4 dose during the study period. Patients with interfering factors were excluded.Thirty cases were enrolled (18 females and 12 males, median age 50 years, median body weight 71 kg, median LT4-C dose 1.71 µg/kg/day). The analysis of patients' age did not reveal differences. LT4-C dose correlated with free-T4 p=0.03) but not with TSH (p=0.42) and free-T3 (p=0.13). TSH was <1.0 mIU/L in 90% of cases. The LT4-C dose-TSH response effect was analysed by probit regression model: the probability to achieve TSH <1.0 mIU/l was 99% with a dose of 1.84 (95%CI 1.57-2.12) µg/kg/day, 75% with a dose of 1.38 µg /kg /day (95%CI 1.17-1.59), and 50% with a dose of 1.20 (95%CI 0.96-1.43). At ROC curve analysis, the most accurate cut-off of LT4-C dose to achieve TSH <1.0 mIU/l was 1.53 ug/kg/day with 70% sensitivity and 100% specificity. Conclusions Athyreotic patients can be initially treated with an LT4-C dose lower than previously stated. Further prospective studies are needed.